D.C. etching anode aluminum foil to form branch tunnels by electroless depositing Cu. Issue 6 (19th August 2019) - Liu, Zhenqi; Wang, Jie; Chen, Jianhan; Liu, Xiya; Yin, Yibin; Ban, Chaolei
Abstract : Purpose: The purpose of this study is to explore the mechanism of branch pits and tunnels formation and increase the specific surface area and capacitance of anode Al foil for high voltage electrolytic capacitor by D.C. etching in acidic solution and neutral. Design/methodology/approach: Al foil was first D.C. etched in HCl-H2 SO4 mixed acidic solution to form main tunnels perpendicular to the Al surface, and then D.C. etched in neutral NaCl solution including 0.5 per cent C6 H8 O7 and Cu(NO3 )2 with different concentration to form branch tunnels normal to Al surface. Between two etching, Cu nuclei were electroless deposited on the interior surface of main tunnels by natural occluded corrosion cell effect to form micro Cu-Al galvanic local cells. The effects of electroless deposited Cu nuclei on cross-section etching morphologies and electrochemical behavior of Al foil was investigated with SEM, polarization curve and electrochemical impedance spectroscopy (EIS). Findings: The results show that sub branch tunnels can form along the main tunnels owing to the formation of Cu-Al micro-batteries, in which Cu is cathode and Al is anode. With increase in Cu(NO3 )2 concentration, more Cu nuclei can be electroless deposited and serve as the favorable sites for branch tunnel initiation along the whole length of main tunnels, leading to enhancement in specific capacitance of anode Al foil. Originality/value: Cu nuclei were electroless deposited on the interior surface of main tunnels by natural occluded corrosion cell effect to form micro Cu-Al galvanic local cells, which can serve as the favorable sites for branch tunnel initiation along the main tunnels to enhance specific capacitance of anode Al foil.